The Effect of Motivation and Organizational Culture on Employee Performance - Ulfatan Sa'adah; Farahsya Dwiyadi (CAKRAWALA : Management Science Journal, 2025)
This research article aims to determine whether motivation has a significant effect on employee performance, whether Organizational Culture has a significant effect on employee performance. The data collection technique used in this study is descriptive qualitative with a predecessor journal as a reference. based on the results of the study it is known that motivation has a partial and significant effect on employee performance. organizational culture has a significant effect on employee performance, The results of this study indicate that motivation and organizational culture have a positive and significant effect on employee performance